Thin film materials : - Freund, L. B (Cambridge University Press, 2003)
This book provides comprehensive coverage of stress, defect formation and surface evolution in thin films. With its balanced coverage of theory, experiment and simulation and many homework problems, the text will be essential reading in senior undergraduate and graduate courses on thin films.